Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's work through the steps to factor the given polynomial [tex]\( P(x) = x^3 + 5x^2 - x - 5 \)[/tex] by grouping.
1. Group the terms:
[tex]\[ P(x) = x^3 + 5x^2 - x - 5 \][/tex]
We will group the polynomial into two sets of terms for easier factoring:
[tex]\[ P(x) = (x^3 + 5x^2) + (-x - 5) \][/tex]
2. Factor each group:
- For the first group [tex]\(x^3 + 5x^2\)[/tex], we can factor out [tex]\(x^2\)[/tex]:
[tex]\[ x^3 + 5x^2 = x^2(x + 5) \][/tex]
- For the second group [tex]\(-x - 5\)[/tex], we can factor out [tex]\(-1\)[/tex]:
[tex]\[ -x - 5 = -1(x + 5) \][/tex]
Thus, the polynomial becomes:
[tex]\[ P(x) = x^2(x + 5) - 1(x + 5) \][/tex]
3. Factor out the common factor [tex]\(x + 5\)[/tex] from the groups:
- Both terms have a common factor of [tex]\(x + 5\)[/tex].
[tex]\[ P(x) = (x^2 - 1)(x + 5) \][/tex]
4. Factor [tex]\(x^2 - 1\)[/tex] as a difference of squares:
- Recall that [tex]\(x^2 - 1\)[/tex] can be factored as [tex]\((x - 1)(x + 1)\)[/tex]:
[tex]\[ x^2 - 1 = (x - 1)(x + 1) \][/tex]
5. Write the final factored form of [tex]\(P(x)\)[/tex]:
- Now combine these factors:
[tex]\[ P(x) = (x - 1)(x + 1)(x + 5) \][/tex]
So, the final factored form of the polynomial [tex]\(P(x) = x^3 + 5x^2 - x - 5\)[/tex] is:
[tex]\[ P(x) = (x - 1)(x + 1)(x + 5) \][/tex]
To summarize the steps as requested in the original layout:
- Grouping:
[tex]\[ P(x) = x^2(x + 5) - 1(x + 5) \][/tex]
- Factoring out the common term:
[tex]\[ P(x) = (x^2 - 1)(x + 5) \][/tex]
- Factoring the difference of squares:
[tex]\[ P(x) = (x - 1)(x + 1)(x + 5) \][/tex]
Thus, completing the steps, we get:
[tex]\[ \begin{array}{l} P(x)=x^2(x + 5) - (x + 5) \\ P(x)=\left(x^2 - 1\right)(x + 5) \\ P(x)=(x - 1)(x+1)(x+5) \end{array} \][/tex]
1. Group the terms:
[tex]\[ P(x) = x^3 + 5x^2 - x - 5 \][/tex]
We will group the polynomial into two sets of terms for easier factoring:
[tex]\[ P(x) = (x^3 + 5x^2) + (-x - 5) \][/tex]
2. Factor each group:
- For the first group [tex]\(x^3 + 5x^2\)[/tex], we can factor out [tex]\(x^2\)[/tex]:
[tex]\[ x^3 + 5x^2 = x^2(x + 5) \][/tex]
- For the second group [tex]\(-x - 5\)[/tex], we can factor out [tex]\(-1\)[/tex]:
[tex]\[ -x - 5 = -1(x + 5) \][/tex]
Thus, the polynomial becomes:
[tex]\[ P(x) = x^2(x + 5) - 1(x + 5) \][/tex]
3. Factor out the common factor [tex]\(x + 5\)[/tex] from the groups:
- Both terms have a common factor of [tex]\(x + 5\)[/tex].
[tex]\[ P(x) = (x^2 - 1)(x + 5) \][/tex]
4. Factor [tex]\(x^2 - 1\)[/tex] as a difference of squares:
- Recall that [tex]\(x^2 - 1\)[/tex] can be factored as [tex]\((x - 1)(x + 1)\)[/tex]:
[tex]\[ x^2 - 1 = (x - 1)(x + 1) \][/tex]
5. Write the final factored form of [tex]\(P(x)\)[/tex]:
- Now combine these factors:
[tex]\[ P(x) = (x - 1)(x + 1)(x + 5) \][/tex]
So, the final factored form of the polynomial [tex]\(P(x) = x^3 + 5x^2 - x - 5\)[/tex] is:
[tex]\[ P(x) = (x - 1)(x + 1)(x + 5) \][/tex]
To summarize the steps as requested in the original layout:
- Grouping:
[tex]\[ P(x) = x^2(x + 5) - 1(x + 5) \][/tex]
- Factoring out the common term:
[tex]\[ P(x) = (x^2 - 1)(x + 5) \][/tex]
- Factoring the difference of squares:
[tex]\[ P(x) = (x - 1)(x + 1)(x + 5) \][/tex]
Thus, completing the steps, we get:
[tex]\[ \begin{array}{l} P(x)=x^2(x + 5) - (x + 5) \\ P(x)=\left(x^2 - 1\right)(x + 5) \\ P(x)=(x - 1)(x+1)(x+5) \end{array} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.